PEACE AND PERFORMANCE (2P) PARADIGM ON ICT PROFESSIONALS - Deveendra Menon A/L Narayanan Nair; Au Yong Hui Nee (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
The two core dependencies of any employee to work happily or even excel in career are Performance and Peace . Peace is defined here as the mental state or stress-free condition for one to use the mind and brain to perform at the optimum level. No one likes to be labeled as a non-performer and no one wants to lose their peace of mind. The need for performance and peace is a natural need in every employee, thus in the new era of human development, following the 2P thirst will be a more suitable and effective method as opposed to forcing and pushing through. The 2P Paradigm wishes to reveal a new vision. The performer and performance should never be separated. Personal Peace and work performance should go together so that the performer performs well. The ultimate aim of Performance is and Peace is an effective means to sustainable Performance In the 2P Paradigm. Both are means and ends. Each is needed and knitted with each other. They are the natural synergizing opposite pairs of order. They should not be separated, like how the protons should not be separated from the electrons in an atom. With the current emphasis on digital economy by the government, ICT organization performance need to be focused. Hence, the 2P paradigm is critically important in ICT organization and department